Chapter 1 A framework for comparing writing curricula cross-nationally - Jeffery, Jill (Taylor & Francis, 2021)
This chapter describes how each case study presented in the volume examined writing curricula situated within one of nine education systems and how we conducted a cross-case comparison of these. We argue that contextualised analyses of curriculum documents, which uncover implicit theories, values, and beliefs about writing development that underpin education policy, are crucial for the innovation of writing research, instruction and curriculum design globally. Further, we propose that cross-national comparisons of school writing curricula illuminate how unique learning cultures and geopolitical settings frame educational policy trajectories that, in turn, shape the teaching of writing across the globe. To ground this volume's project theoretically, we begin with a consideration of the ways that writing development has been conceptualised and what pedagogical approaches might follow. To introduce the volume's methodological approach, we then discuss sources of information provided by government education agencies and their proxies to represent writing curricula; the varying ways in which these are developed within school systems; and how we might expect these to influence writing instruction in schools. We conclude by detailing the volume's framework for within- and cross-case analyses of curriculum documents in New Zealand, Chile, Hong Kong, the United States, Uzbekistan, Germany, England, Denmark and Norway.